The Demolition of Kirkuk Citadel: A Displaced Memory – A Documentary Study of the Policy of Ethnic Cleansing 1990-1998 - Abdulaziz, Prof.Dr. Dilshad Omar (Sulaimani Journal for Humanities, 2025)
The study lies in highlighting a major cultural and civilizational crime committed against the Kirkuk Citadel through a political decision by the former Iraqi president during his visit to the city of Kirkuk on March 16, 1990, to demolish the citadel. Accordingly, the local administration in the city formed a committee to carry out the demolition of residential buildings and heritage sites the following day, and allocated funds for it. The demolition process of the Kirkuk Citadel began in two phases, the first phase started in 1990, and the second phase in 1998. The study aims to reveal the political and professional reasons and motives behind the decision to demolish the Kirkuk Citadel, and to analyze the role played by the policy of ethnic and cultural cleansing in making the decision, and its impact on human heritage, based on official documents, through the main axes of the study. The first axis deals with a historical overview of the Kirkuk Citadel: its historical and cultural significance, and the most prominent stages it went through. The second axis addresses the stages of the demolition of the Kirkuk Citadel and analyzes the political and cultural motives behind the demolition process. The third axis deals with the impact of the demolition of the citadel on the cultural, ethnic, and historical heritage of the city, and on erasing the ethnic cleansing.
Keywords: Iraq; Kurds; Kirkuk Citadel; Ethnic cleansing; Cultural cleansing